(untitled) (Journal of Economic Research & Business Administration, 2016)
The article examines the project management as a tool for effective functioning and implementation of active investment and innovation functions of enterprises. The author collected and compiled a set of concepts within the projects and project management. Also, the author offers a classification on the basis of project risks and causes symptoms, relative to project management. These include projects focus on specific results, especially the result of the project, product, service, limited project time factor, the sequence of the project processes. The author also considers the process management in two aspects. The first aspect is the current management, the second Probable project management of the enterprise. If, especially the process of ongoing management is the business processes that take place within the framework of daily work, the design processes include processes aimed at improvement of current works, in accordance with the strategic goals of organizations. As part of the article it was offered an effective model based on the classification of the project risks, which can help to improve the quality of assessment, analysis and monitoring of project management.